2014
DOI: 10.1007/s10439-014-1074-9
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Heat and Water Vapor Transfer in MDCT-Based Human Airway Models

Abstract: A three-dimensional (3D) thermo-fluid model is developed to study regional distributions of temperature and water vapor in three multi-detector row computed-tomography (MDCT)-basedhuman airwayswith minute ventilations of 6, 15 and 30 L/min. A one-dimensional (1D) model is also solved to provide necessary initial and boundary conditionsforthe 3D model. Both 3D and 1D predicted temperature distributions agree well with available in vivo measurement data. On inspiration, the 3D cold high-speed air stream is split… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 27 publications
8
60
0
Order By: Relevance
“…The three subjects were the same subjects used in a previous computational study. 28 All subjects were normal non-smokers: subject A was a 32 year-old male with BMI of 21.6; subject B was a 20 year-old male with BMI of 22.33; subject C was a 32 year-old female with BMI of 26.63. Imaging was acquired with the subjects placed in the supine body posture and coached to breath-hold near total lung capacity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The three subjects were the same subjects used in a previous computational study. 28 All subjects were normal non-smokers: subject A was a 32 year-old male with BMI of 21.6; subject B was a 20 year-old male with BMI of 22.33; subject C was a 32 year-old female with BMI of 26.63. Imaging was acquired with the subjects placed in the supine body posture and coached to breath-hold near total lung capacity.…”
Section: Methodsmentioning
confidence: 99%
“…One such assumption is axisymmetric air velocity, temperature, and humidity profiles in the airway radial direction, whereas previous studies have shown non-axisymmetric distributions especially near bifurcations. 28 Second, 1D and 2D geometric models lack many 3D geometric features, such as variation in cross-sectional area along an airway, curvature, and non-circular cross-sectional profiles. Moreover, most previous studies 6,8 have been limited to Weibel’s symmetric airway model, 26 and do not account for inter-subject variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While image registration can provide information on regional ventilation and lung deformation, computational fluid dynamics (CFD) models can provide information regarding gas flow, particle transport, and heat transfer in the human lung (Lin et al (2007), Miyawaki et al (2012), Wu et al (2014)). For example, CFD-based models can predict the location of particle deposition on the airway wall to investigate the regional differences associated with specific particulate matter, e.g., aerosolized pharmaceutical drugs and pollutants, to the human lung.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the airflow characteristics, along with the density and the deposition of the particles on the respiratory airways, are discerned. As of today, various CFD models have been employed to analyze the function of the lungs in terms of inspiration and expiration [10]- [12]. Also, several approaches, based on the data acquired by the CFD analysis, introduce calculations of the particles features [13]- [16].…”
Section: Introductionmentioning
confidence: 99%